Long non-coding RNA exchange during the oocyte-to-embryo transition in mice - Karlic, Rosa; Ganesh, Sravya; Franke, Vedran; Svobodova, Eliska; Urbanova, Jana; Suzuki, Yutaka; Aoki, Fugaku; Vlahovicek, Kristian; Svoboda, Petr (DNA research, 2017)
The oocyte-to-embryo transition (OET) transforms a differentiated gamete into pluripotent blastomeres. The accompanying maternal-zygotic RNA exchange involves remodeling of the long non-coding RNA (lncRNA) pool. Here, we used next generation sequencing and de novo transcript assembly to define the core population of 1,600 lncRNAs expressed during the OET (lncRNAs). Relative to mRNAs, OET lncRNAs were less expressed and had shorter transcripts, mainly due to fewer exons and shorter 5' terminal exons. Approximately half of OET lncRNA promoters originated in retrotransposons suggesting their recent emergence. Except for a small group of ubiquitous lncRNAs, maternal and zygotic lncRNAs formed two distinct populations. The bulk of maternal lncRNAs was degraded before the zygotic genome activation. Interestingly, maternal lncRNAs seemed to undergo cytoplasmic polyadenylation observed for dormant mRNAs. We also identified lncRNAs giving rise to trans-acting short interfering RNAs, which represent a novel lncRNA category. Altogether, we defined the core OET lncRNA transcriptome and characterized its remodeling during early development. Our results are consistent with the notion that rapidly evolving lncRNAs constitute signatures of cells-of-origin while a minority plays an active role in control of gene expression across OET. Our data presented here provide an excellent source for further OET lncRNA studies.
Keywords: endo-siRNA; sekvenční analýza RNA; blastomery; polyadenylation; embryo savčí; oocyty; Blastomeres; vývojová regulace genové exprese; High-Throughput Nucleotide Sequencing; Gene Expression Regulation, Developmental; RNA dlouhá nekódující; Embryo, Mammalian; zygote; RNA, Long Noncoding; stanovení celkové genové exprese; lncRNA; oocyte; Gene Expression Profiling; Animals; zvířata; vysoce účinné nukleotidové sekvenování; myši; Sequence Analysis, RNA; Mice; Oocytes